2016
DOI: 10.18632/oncotarget.8941
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-93 inhibits ischemia-reperfusion induced cardiomyocyte apoptosis by targeting PTEN

Abstract: MicroRNAs have been implicated in some biological and pathological processes, including the myocardial ischemia/reperfusion (I/R) injury. Recent findings demonstrated that miR-93 might provide a potential cardioprotective effect on ischemic heart disease. This study was to investigate the role of miR-93 in I/R-induced cardiomyocyte injury and the potential mechanism. In this study, we found that hypoxia/reoxygenation (H/R) dramatically increased LDH release, MDA contents, ROS generation, and endoplasmic reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 17 publications
3
69
0
Order By: Relevance
“…In previous years, an increasing number of studies focusing on the upstream regulatory factors of PTEN have revealed that certain lncRNAs and miRNAs may regulate their expression in a variety of ways. Ke et al (45) indicated that miR-93 may protect against HR-induced cardiomyocyte apoptosis by inhibiting the PI3K/AKT/PTEN signaling pathway. It has also been reported that lncRNAs may directly or indirectly regulate PTEN during apoptosis in tumor cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…In previous years, an increasing number of studies focusing on the upstream regulatory factors of PTEN have revealed that certain lncRNAs and miRNAs may regulate their expression in a variety of ways. Ke et al (45) indicated that miR-93 may protect against HR-induced cardiomyocyte apoptosis by inhibiting the PI3K/AKT/PTEN signaling pathway. It has also been reported that lncRNAs may directly or indirectly regulate PTEN during apoptosis in tumor cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, by detecting the activities of serum myocardial enzymes that are regarded as markers of ischemic myocardial damage, we found that the expression level of miR-24-3p in ischemia/reperfusion mice was negatively correlated with the levels of serum lactate dehydrogenase, creatine kinase and creatine kinase-mb form (LDH, CK and CK-MB) [18,19]. Patients with ischemic heart disease usually suffer from myocardial reperfusion after therapy, which might result in acute myocardial damage and adverse ventricular remodeling [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the reduced S‐sulfhydration, Akt activity increased significantly (Ohno et al, ). As far as we know, PTEN is also a key signal molecular in cardiomyocyte apoptosis (Ke et al, ), ventricular remodelling (Yang et al, ), angiogenesis (Serra et al, ) and other cardiovascular diseases. It is thought that protein S‐sulfhydration and S‐nitrosylation of PTEN keep a dynamic balance, and compete with each other to maintain normal function of the protein.…”
Section: Crosstalk With Protein S‐sulfhydration and Other Post‐translmentioning
confidence: 99%